A method for wafer assignment in semiconductor wafer fabrication considering both quality and productivity perspectives. (July 2019) - Lee, Dong-Hee; Lee, Chang-Ho; Choi, Seung-Hyun; Kim, Kwang-Jae
Highlights: Wafers are assigned to machines by considering both quality and productivity perspectives. Wafer yield and line balancing index are used for quality and productivity perspectives, respectively. High wafer yield is achieved while satisfying a user defined level for line balancing. Abstract: In the semiconductor wafer fabrication process, wafers go through a series of sequential process steps. Typically, each process step has several machines, and the wafers are assigned to one whenever they enter the process step. When assigning wafers to machines, it is important to consider both the quality and productivity perspectives. Major semiconductor companies in Korea have recently implemented a wafer assignment system to improve wafer yield, a critical measure for semiconductor quality. This system, however, does not consider the productivity perspective. This paper presents a systematic method for assigning wafers to maximize the wafer yield while satisfying a predetermined target level of productivity. A simple hypothetical example is presented to illustrate the method.